2021
DOI: 10.5944/educxx1.28514
|View full text |Cite
|
Sign up to set email alerts
|

Mitos del amor romántico en adolescentes: relación con el sexismo y variables procedentes de la socialización

Abstract: Los mitos del amor romántico pueden actuar como un guion con el que orientar los pensamientos, los sentimientos y los comportamientos en las relaciones de pareja. El objetivo de la presente investigación fue analizar la aceptación de los mitos románticos y su relación con el sexismo y otras variables procedentes de la socialización en la población adolescente de Castilla-La Mancha. La investigación cuenta con una muestra representativa de 1840 estudiantes de Educación Secundaria Obligatoria, con una edad media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
(39 reference statements)
1
2
0
3
Order By: Relevance
“…However, according to the present study, religion does not always act in favor of violence prevention, if we observe the data obtained in the perpetration of this, we identify that those who belong to the Muslim religion recognize that they eliminate or block friends of their partners to prevent them from having contact with them to a greater extent than those who do not process any religion. These findings are in line with several studies that identify that sexist attitude increases as religiosity does [ 3 , 29 , 30 , 65 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, according to the present study, religion does not always act in favor of violence prevention, if we observe the data obtained in the perpetration of this, we identify that those who belong to the Muslim religion recognize that they eliminate or block friends of their partners to prevent them from having contact with them to a greater extent than those who do not process any religion. These findings are in line with several studies that identify that sexist attitude increases as religiosity does [ 3 , 29 , 30 , 65 ].…”
Section: Discussionsupporting
confidence: 92%
“…Boys acknowledge having committed more relational and sexual violence, while girls report more physical and verbal-emotional violence [ 8 , 28 ]. If we consider the relationship between religion and sexist attitudes, several studies conducted in different contexts indicate that the existence of religious beliefs contributes to an increase in sexist attitudes [ 3 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the barriers related to the socialization process of young women and those derived from the process of leaving the situation of violence itself, it has been found that this type of violence is more normalized in this age group than in others due to false beliefs about how love relationships are built. Control and jealousy behaviours are normalized as signs of love, thus posing a barrier for young women to identify this type of violence and seek help [ 16 , 31 , 32 ]. On the other hand, an important barrier is the lack of knowledge about the resources available to leave the situation of violence.…”
Section: Discussionmentioning
confidence: 99%
“…El rol de las instituciones en el abordaje de la sexualidad es fundamental (León y Aizpurúa, 2020;Bonilla-Algovia, 2021) para erradicar la lacra del sexismo, la homofobia, la violencia de género. Con este trabajo se pretende constatar, nuevamente, la necesidad de dicho abordaje en la enseñanza infantil, primaria y secundaria, sustentándolo también en la necesidad, en primer lugar, de hacerlo con aquellos/as futuros profesionales de la Educación que están ahora mismo formándose.…”
Section: Discusión Y Conclusionesunclassified